Genomic comparison of gamma-aminobutyric acid-producing Levilactobacillus brevis and Companilactobacillus zhachilii strains from Thai fermented foods - Pakdeeto, Amnat; Phuengjayaem, Sukanya; Kingkaew, Engkarat; Tungkajiwangkoon, Santhita; Phitchayaphon, Chantharat; Tanasupawat, Somboon (Agriculture and Natural Resources, 2025)
Importance of the work: The GABA-producing Companilactobacillus zhachilii isolated from fermented pork (‘nham’) demonstrates both efficacy and safety in GABA production. Objectives: To identify the GABA-producing strains ASK-1 and ANB-1 to compare their genomes with those of Levilactobacillus brevis and Companilactobacillus zhachilii strains. Materials and Methods: Two fermented food samples were collected and used for the isolation of lactic acid bacteria. The strains obtained were evaluated for GABA production. The selected strains were identified based on their phenotypic and genotypic characteristics. Genomic comparisons of the GABA-producing strains were performed using genome sequencing, assembly, annotation and comparative analysis. This analysis included the examination of CRISPR regions, antimicrobial genes, functional attributes and genome visualization. Results: The GABA-producing lactic acid bacteria (ASK-1 and ANB-1) were isolated from traditional Thai fermented foods (‘sai-krog-prieo’ and ‘nham’). The strains ASK-1 and ANB-1 produced 9.12 ± 0.51 g/L GABA and 12.73 ± 0.57 g/L GABA, respectively. On the basis of phenotypic characteristics and 16S rRNA gene sequencing, strain ASK-1 presented 100% sequence similarity to Levilactobacillus brevis ATCC 14687T, whereas ANB-1 presented 99.93% similarity to Companilactobacillus zhachilii HBUAS52074ᵀ. Genome analysis identified ASK-1 as L. brevis ATCC 367, with an average nucleotide identity based on a BLAST (ANIb) value of 98.86% and ANB-1 with an ANIb value of 96.92%, to C. zhachilii HBUAS52074ᵀ. Additionally, genomic studies revealed GABA-producing genes (gadA and gadB) via the KofamKOALA-KEGG Orthology database. Main finding: Levilactobacillus brevis ASK-1 and Companilactobacillus zhachilii ANB-1 efficiently and safely produced GABA and exhibited probiotic properties, making them promising starter cultures for functional food production in both local food and industrial fermentation processes.